Beyond traditional biology instruction: a mixed-methods comparative study on virtual reality's impact on high school students' habits of mind - Neiroukh, Nader Mohamad Issa; Ayyoub, Abedalkarim (Frontiers in Education, 2025)
This mixed-method quasi-experimental study investigated the effects of virtual reality immersion (VRI) in biology classes on East Jerusalem high school students' scientific habits of mind, specifically self-regulation, critical thinking, and creative thinking. The study was grounded in the Cognitive Affective Model of Immersive Learning (CAMIL), which emphasizes how immersive environments enhance cognitive and affective engagement. A random cluster sample of 207 male and female students from three East Jerusalem high schools (two male and one female) participated in the study. Over a four-month period, participants were exposed to VRI-based biology content designed according to CAMIL principles. Data were collected using pre- and post-tests to measure changes in students' self-regulation, critical thinking, and creative thinking. A mixed-method design was employed to capture both measurable outcomes and students' lived experiences, integrating quantitative results with qualitative insights to ensure methodological triangulation. Quantitative analysis using the non-parametric Wilcoxon Signed-Rank Test revealed statistically significant and substantial improvements in students' self-regulation, critical thinking, and creative thinking following the integration of VRI. Qualitative findings supported these outcomes, highlighting students' positive perceptions and experiences with immersive biology learning. The findings demonstrate that incorporating VRI into biology instruction can meaningfully enhance students' higher-order thinking skills and scientific habits of mind. These results suggest the potential of VRI to encourage greater student interest and enrollment in scientific tracks. However, further research is recommended across other science subjects (e.g., physics, chemistry, and mathematics) to validate the broader applicability of these results. Educators and researchers are encouraged to explore VRI integration to foster students' cognitive growth and promote pursuit of higher education in scientific domains.